The body in parts: fantasies of corporeality in early modern Europe - Hillman, David (Routledge, 1997)
Introduction : individual parts / David Hillman and Carla Mazzio -- Members only / Nancy J. Vickers -- Out of joint / Marjorie Garber -- Sins of the tongue / Carla Mazzio -- Visceral knowledge / David Hillman -- Nervous tension / Gail Kern Paster -- Is the fundament a grave? / Jeffrey Masten -- Missing the breast / Kathryn Schwarz -- The rediscovery of the clitoris / Katharine Park -- Taming the basilisk / Sergei Lobanov-Rostovsky -- Mutilation and meaning / Stephen Greenblatt -- Fables of the belly in early modern England / Michael Schoenfeldt -- Sacred heart and secular brain / Scott Manning Stevens -- "God's handy worke" / Katherine Rowe